The Quantification of Lead Heavy Metals Levels on Mujair Fish (Oreochromis mossambicus) Organs From Brantas and Bengawan Solo River, East Java Province, Indonesia - Setiyowati, Putri Ayu Ika; Ramadani, Aisyah Hadi; Suhariyati, Suhariyati; Mahbubillah, M Ainul (Al-Kauniyah: Jurnal Biologi, 2024)
AbstractOreochromis mossambicus (O. mossambicus) frequently found in the Brantas and Bengawan Solo rivers, Java island, Indonesia. However, heavy metals produced from anthropogenic activities can enter the water and accumulate in organisms living in the river. This study aimed to determine the lead (Pb) heavy metal in the gills, flesh, and intestines of O. mossambicus living in the two aforementioned rivers and to measure the Pb levels in each river. The results showed that the Pb in the O. mossambicus organs in the Bengawan Solo river was as follows 3.159 mg/kg in the gills; 1.930 mg/kg in the intestine; and 2.511 mg/kg in flesh, while in the Brantas river it was follows 1.600 mg/kg in gills; 1.402 mg/kg in the intestine; and 1.455 mg/kg flesh. Pb levels in each river water were 0.568 mg/mL in the Brantas river and 0.525 mg/mL in the Bengawan Solo river. Based on the data obtained, it can be concluded that the Pb content in fish organs and river water has exceeded the quality standard for Pb levels according to the government regulation No.82 2001 (SNI 7387:2009), that is, 0.3 mg/kg in organs and 0.03 mg/L in water. The results of this study are expected to be a concern for the authorities in order to revitalize the river to restore the function and support the survival of river biota.AbstrakIkan mujair (Oreochromis mossambicus) banyak ditemukan di sungai Brantas dan Bengawan Solo, namun aktivitas antropogenik yang menghasilkan logam berat dapat masuk ke perairan sehingga terakumulasi dalam organisme yang hidup di perairan tersebut. Penelitian ini bertujuan untuk mengetahui kandungan logam berat timbal (Pb) pada insang, daging, dan usus pada O. Mossambicus yang hidup di kedua sungai tersebut serta mengukur kandungan Pb pada masing-masing air sungai. Hasil penelitian menunjukkan bahwa kandungan Pb pada organ O. mossambicus di sungai Bengawan Solo adalah sebagai berikut 3.159 mg/kg pada insang; 1.930 mg/kg di usus; dan 2.511 mg/kg pada daging, sedangkan di sungai Brantas adalah sebagai berikut 1.600 mg/kg pada insang; 1,402 mg/kg pada usus; dan 1,455 mg/kg pada daging. Kadar Pb pada masing-masing air sungai adalah 0,568 mg/mL (sungai Brantas) dan 0,525 mg/mL (sungai Bengawan Solo). Berdasarkan data yang diperoleh dapat disimpulkan bahwa kandungan Pb pada organ ikan maupun air sungai sudah melebihi baku mutu kadar Pb pada organ yaitu 0,3 mg/kg (SNI 7387:2009) dan 0,03 mg/L pada perairan (PP No.82 tahun 2001). Hasil penelitian ini diharapkan dapat menjadi perhatian pihak-pihak terkait agar dapat melakukan revitalisasi sungai guna mengembalikan fungsi dan mendukung keberlangsungan hidup biota sungai.